Biofilm formation by Salmonella spp. in catfish mucus extract under industrial conditions. (April 2018) - Dhowlaghar, Nitin; De Abrew Abeysundara, Piumi; Nannapaneni, Ramakrishna; Schilling, Mark W.; Chang, Sam; Cheng, Wen-Hsing; Sharma, Chander S.
Abstract: The objective of this study was to determine the effect of strain and temperature on the growth and biofilm formation of Salmonella spp. in high and low concentrations of catfish mucus extract on different food-contact surfaces at 22 °C and 10 °C. The second objective of this study was to evaluate the efficacy of disinfectants at recommended concentrations and contact times for removing Salmonella biofilms cells on a stainless steel surface containing catfish mucus extract. Growth and biofilm formation of all Salmonella strains increased with higher concentrations of catfish mucus extract at both 10 °C and 22 °C. In 15 μg/ml of catfish mucus extract inoculated with 3 log CFU/ml, the biofilm levels of Salmonella on stainless steel surface reached to 3.5 log CFU/cm 2 at 10 °C or 5.5 log CFU/cm 2 at 22 °C in 7 days. In 375 μg/ml of catfish mucus extract inoculated with 3 log CFU/ml, the biofilm levels of Salmonella on the stainless steel surface reached 4.5 log CFU/cm 2 at 10 °C and 6.5 log CFU/cm 2 at 22 °C in 7 days. No differences were observed between Salmonella strains tested for biofilm formation in catfish mucus extract on the stainless steel surface. The biofilm formation by Salmonella Blockley (7175) in catfish mucus extract was less ( P < 0.05) on buna-N rubber when compared to stainless steel, polyethylene and polyurethane surfaces. Salmonella biofilm cells were not detectable on the stainless steel surface after treatment with a mixture of disinfectants but were still present when single compound disinfectants were used. Highlights: Salmonella uses catfish mucus as a nutrient source for growth and biofilm formation on different food-contact surfaces. Salmonella serotype Blockley biofilm formation in catfish mucus extract was least on buna-N rubber. No differences in biofilm formation were observed among six Salmonella strains in catfish mucus extract. Growth and biofilm formation of Salmonella spp. increased with increasing concentration of catfish mucus at 22°C and 10°C.